2011
DOI: 10.1161/circep.110.959338
|View full text |Cite
|
Sign up to set email alerts
|

ECG Identification of Scar-Related Ventricular Tachycardia With a Left Bundle-Branch Block Configuration

Abstract: Background-A left bundle-branch block (LBBB)-like pattern with a dominant S-wave in V 1 is common in idiopathic ventricular arrhythmias (VA). Discrimination between idiopathic and scar-related LBBB pattern VA has important clinical implications. We hypothesized that the VA QRS morphology is influenced by the presence of ventricular scar, allowing ECG discrimination of VA arising from structurally normal versus scarred myocardium. Methods and Results-Twelve-lead ECGs of 297 LBBB pattern monomorphic VA were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
11
0
4
Order By: Relevance
“…VAs with RBBB morphology and superior QRS axis are indeed consistent with an inferior LV wall exit, which have been rarely observed in idiopathic VAs. 26 Interestingly, this matches with the observation that LV segments having LGE were frequently located in the inferior and inferolateral wall, suggesting the possible relationship of reentry circuits to the detected scar.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…VAs with RBBB morphology and superior QRS axis are indeed consistent with an inferior LV wall exit, which have been rarely observed in idiopathic VAs. 26 Interestingly, this matches with the observation that LV segments having LGE were frequently located in the inferior and inferolateral wall, suggesting the possible relationship of reentry circuits to the detected scar.…”
Section: Discussionsupporting
confidence: 85%
“…VAs with RBBB morphology and superior QRS axis are indeed consistent with an inferior LV wall exit, which have been rarely observed in idiopathic VAs. 26 Interestingly, this matches with the observation that LV segments having LGE were frequently located in the inferior and inferolateral wall, suggesting the possible relationship of reentry circuits to the detected scar.Another important finding of this study is that the presence of myocardial structural abnormalities on cMRI was a predictor of follow-up arrhythmic events among patients presenting with apparently idiopathic VAs. This finding fits with observations of previous studies that cMRI is able to identify patients at risk for arrhythmic events in several overt heart diseases, including ischemic cardiomyopathy, nonischemic dilated cardiomyopathy, hypertrophic cardiomyopathy, and myocarditis.…”
supporting
confidence: 85%
“…7 Other ECG features suggestive of an origin at the epicardial aspect of the LV outflow tract include R wave width >85 ms, 8 presence of q wave in lead I, 9 and, specifically, aVL/aVR amplitude ratio >1.75, indicating an origin at the upper part of the LV summit. Nevertheless, QRS morphology may be influenced by the presence and extent of myocardial scar, which can be predicted by the presence of a late precordial transition, precordial notching, and a QRS-S interval >90 ms. 10 Finally, the ECG features of the tachycardia were remarkably similar to the PVCs, suggesting a common site of origin for these arrhythmias, as does the elimination of one of them when targeting the other, making PVC ablation a more than acceptable surrogate in the case that the clinical SMVT is not inducible. 5 Although the majority of idiopathic VTs originate in hearts without structural disease, a small subset can occur in conjunction with different entities such as coronary artery disease, valvular regurgitation or LV dysfunction, or abnormal MRI findings.…”
Section: Discussion and Teaching Pointsmentioning
confidence: 83%
“…Nevertheless, QRS morphology may be influenced by the presence and extent of myocardial scar, which can be predicted by the presence of a late precordial transition, precordial notching, and a QRS-S interval >90 ms. 10 Finally, the ECG features of the tachycardia were remarkably similar to the PVCs, suggesting a common site of origin for these arrhythmias, as does the elimination of one of them when targeting the other, making PVC ablation a more than acceptable surrogate in the case that the clinical SMVT is not inducible.…”
Section: Management Of Left Ventricular Summit Tachycardias E83mentioning
confidence: 83%
“…In this research, we involved more VAs arising from the free wall of RVOT, and found using the presence of notching to differentiate the two conditions was not enough. In another study conducted by Wijnmaalen et al., the total number of leads expressing QRS notching during VA did not get statistically significant between the scar and nonscar groups either.…”
Section: Discussionmentioning
confidence: 78%